(untitled) ("Conference on Universal Science Research 2023", 2023)
The present article is about the linguo cultural peculiarities of the speech etiquette units in the English. The author of the article discusses the role of the speech etiquette units in the process of communication. The ways of expressing gratitude, appreciation, asking a request in the two languages are also discussed in the article. The structure and semantic peculiarities of speech etiquette units of the English and Russian languages are also discussed in the article. The author of the article claims that the speech etiquette units are to be discussed thoroughly and given in the practical English books